2009
DOI: 10.1111/j.1468-5965.2009.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Cities, Europeanization and Multi‐level Governance: Governing Climate Change through Transnational Municipal Networks*

Abstract: This article focuses on a variant of multi-level governance and Europeanization, i.e. the transnational networking of local authorities. Focusing on local climate change policy, the article examines how transnational municipal networks (TMNs) govern in the context of multi-level European governance. We find that TMNs are networks of pioneers for pioneers. Copyright (c) 2009 The Author(s). Journal compilation (c) 2009 Blackwell Publishing Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
358
0
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 528 publications
(401 citation statements)
references
References 32 publications
5
358
0
12
Order By: Relevance
“…Results regarding the mitigation dimension on local actions reveal six factors: the municipality having set ambitious policy goals, municipalities having experienced staff members, the municipality engaging in partnership with local business firms, the municipality having collaborative ties with other municipalities, the municipality having memberships of international climate change issue networks, and the municipality using intergovernmental support schemes issued by higher level governments. Whereas the first three of the factors mentioned can be classified as 'localist', the other three reveal the importance of efforts local government makes that goes beyond the local level (concerning the 'multi-level' and 'issue network' dimensions; which is in line with [18,19,91]). …”
Section: Results Of the Comparative Analysis On Factors Enabling Locamentioning
confidence: 83%
See 3 more Smart Citations
“…Results regarding the mitigation dimension on local actions reveal six factors: the municipality having set ambitious policy goals, municipalities having experienced staff members, the municipality engaging in partnership with local business firms, the municipality having collaborative ties with other municipalities, the municipality having memberships of international climate change issue networks, and the municipality using intergovernmental support schemes issued by higher level governments. Whereas the first three of the factors mentioned can be classified as 'localist', the other three reveal the importance of efforts local government makes that goes beyond the local level (concerning the 'multi-level' and 'issue network' dimensions; which is in line with [18,19,91]). …”
Section: Results Of the Comparative Analysis On Factors Enabling Locamentioning
confidence: 83%
“…Kern and Bulkeley [18] found that membership of international climate change issue networks (like ICLEI or Covenant of Mayors) had a positive impact. Local government staff members become better informed about state-of-the-art developments, and increase adaptive capacity to learn from best practices and adopt them in their very own localities.…”
Section: Cluster Iv: External Issue Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…International bargaining links subnational policy levels in all countries 37 Andonova and Mitchell 2010;Kern andBulkeley 2009. 38 Schaffer 2011.…”
Section: Extensions and Empirically Falsifiable Implicationsmentioning
confidence: 99%